A trip through the challenges of smart solutions for emergency and crisis management - Villela, Karina (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2014)
Emergencies are defined as critical situations caused by incidents, natural or man-made, that require measures to be taken immediately to reduce their adverse consequences to life and property. Examples of natural incidents are floods, wildfires, and snow storms, whereas examples of man-made incidents are fires, explosions and/or substance spills from oil platforms, ships, and factories. In large-scale events, the risk of crowd-inherent incidents such as conflicts between opposing crowds in football matches or mass panic is of particular concern. A crisis is the adverse and therefore undesired consequences of an emergency.